OCCURRENCE OF THE PUERULUS LARVAE OF THE INDIAN SPINY LOBSTER, PANUURUS HOMARVS (LINN.), IN COCHIN BACKWATER - Kathirvel, M (Indian Journal of Fisheries, 2011)
The occurrence of puerulus larvae of the Indian spiny lobster, Panulirus homarus (Linn.) in ttÂ» Cochin backwater is reported. Being the first record of these larvae frcmi Indian waters, brief notes on the puerulus, its metamorphosis to postpuerulus